Results of Amultidisciplinary Antimicrobial Stewardship Program - Lobo, Letícia Gomes (2017)
Background and Objectives: The aim of this study was to evaluate the results of the PCA developed by the Infection Control Service of a university hospital in southern Brazil from January / 2013 to July / 2014. Methods: The PCA is developed by two doctors and a pharmacist infectious disease. They are evaluated all prescriptions carbapenems, vancomycin, polymyxin B, daptomycin, tigecycline, linezolid, voriconazole, micafungin and amphotericin b lipid complex. In need of intervention the same is conducted by telephone with guidance to prescribers or alert in the electronic medical record. Moreover, they are made rounds with teams of cardiac intensive care unit (ICU-CV) for case discussion. Results and Conclusion: 5118 requirements were evaluated with an average of 297 prescriptions month. The percentage of crops request in half 1 (January to June / 13), 2 (July to December / 13) and 3 (January to July / 14) was respectively 25%, 35% and 83%. on average they were performed 70 operations / month, where the percentage of accepted interventions in the semester 1,2 and 3 was respectively 61%, 70% and 84%. The defined daily dose (DDD) of meropenem in UTI-CV for the period was 231.4 DDD / 1000 patient-days in semestre1, 108.13 DDD / 1000 patient-days in semester 2 and 83.79 DDD / 1000-patient -day in half 3.Nossos data allow to conclude that actions such as encouraging the targeted treatment (culture collection), education and feedback to prescribers (guiding the rational use) and active participation in rounds together the care teams can be strategies in the fight against the resistance. KEY WORDS: Infection control. Anti-Infective Agents. Interdisciplinary research.